Reproductive Performances and Egg Qualities in African Catfish (Clarias gariepinus) Broodstocks Supplemented with Curcumin and Thyroxine Hormone - Livana Dethris Rawung; Damiana Rita Ekastuti; Muhammad Zairin Junior; Min Rahminiwati; Ade Sunarma; Wasmen Manalu (Journal Omni-Akuatika, 2020)
An experiment was designed to study the effects of curcumin and thyroxine hormone supplementation in the diet to improve the reproductive performance of catfish broodstock by improving egg quality that eventually increases the production of seedlings. Catfish used in this experiment were supplemented with curcumin and thyroxine hormone through their feeds for 12 weeks. The results showed that there was no significant difference (p > 0.05) in the hepatosomatic index (HSI), gonadosomatic index (GSI), percentage of gonad maturity, total cholesterol concentration in the spawned eggs, high density lipoprotein (HDL) concentration in the spawned eggs, fertilization rate of spawned eggs, and hatching rate of fertilized eggs.  However, there were significant differences (p < 0.05) in the concentration of vitellogenin in the spawned eggs, egg diameter of the spawned eggs, and the triglycerides contents of spawned eggs. It was concluded that curcumin and thyroxine supplementations of African catfish increased vitellogenin concentrations and diameters of spawned eggs that have great potential to improve the reproductive performance.